Application of selected components of “SPICES” model as teaching-learning method in pharmacology (Bangladesh Journal of Pharmacology, 2021)
This study was to compare the performance of the students (future pres-cribers) of four medical colleges using three modules on rational prescribing. Marks obtained (out of 35) in ‘student-centered learning’ approach in first and second assessment were 28.3 ± 3.4 and 23.7 ± 4.2 respectively, which is significantly (p